Platelet rich plasma (PLP) and its growth factors another breakthrough in medicine - Meimban, Cynthia Aguilar (The Journal of the Philippine Dental Association)
Platelets-Rich Plasma and its growth factors is another breakthrough in medicine. This article will present its repsonse to injury and the healing or growth factors arising from platelets.